Three-dimensional ultrasound-based radiomics nomogram for the prediction of extrathyroidal extension features in papillary thyroid cancer - Lu, Wen-Jie; Mao, Lin; Li, Jin; OuYang, Liang-Yan; Chen, Jia-Yao; Chen, Shi-Yan; Lin, Yun-Yong; Wu, Yi-Wen; Chen, Shao-Na; Qiu, Shao-Dong; Chen, Fei (Frontiers in Oncology, 2023)
Purpose: To develop and validate a three-dimension ultrasound(3D US) radiomics nomogram for the preoperative prediction of extrathyroidal extension (ETE) in papillary thyroid cancer (PTC). Methods：This retrospective study included 168 patients (non ETE, n = 90; ETE, n = 78) whom were divided into training (n =117) and validation (n =51) cohorts with surgically proven PTC by a random stratified sampling strategy. The regions of interests (ROIs) were obtained manually from 3D US images. A larger number of radiomic features were automatically extracted. Finally, a nomogram was built incorporating the Key Words: three-dimension ultrasound,radiomics, nomogram,extrathyroidal extension, papillary thyroid cancerPTC is the most common endocrine malignant tumor, and its incidence rate is increasing all over the world (1) .The reason for this increase in incidence is partly because of the popularization of routine physical examination and the improvement of high-frequency ultrasound (2). Most PTC patients have a good prognosis, more than 90% of them have survived for more than 10 years (3). Although PTC has a favorable prognosis, some cases show aggressive clinical features, such as lymph node and distance metastasis, and poorer prognosis (4). ETE has long been considered to be an independent predictor of poor prognosis PTC patients (5). Also, ETE is regarded to be the important risk factor associated with recurrence and metastasis, and it has an important impact on staging and the choice of operation (6). The recurrence and mortality after surgery will increase in ETE patient. The 15-year survival rate among PTC patients with ETE was significantly worse than in patients without ETE (7, 8). Traditional surgical setting includes total and subtotal thyroidectomies for PTC, according to the National Comprehensive Cancer Network (NCCN) Guidelines for Thyroid Carcinoma (3rd Edition, 2018), total thyroidectomy is the best method to treat ETE patients in PTC (7). Though both surgical procedures have no significant effect on distant metastasis and cancer-